The role of sensory experience in presynaptic development is cortical area specific - Cheetham, Claire E J (Blackwell Science Inc, 2011)
ABSTRACT: The postsynaptic response to a stimulus is dependent on the history of previous activity at that synapse. This short-term plasticity (STP) is a key determinant of neural network function. During postnatal development, many excitatory intracortical synapses switch from strong depression during early postnatal life, to weaker depression and in some cases facilitation in adulthood. However, it is not known whether this developmental switch is an innate feature of synaptic maturation, or whether it requires activity. We investigated this question in the barrel and visual cortex, two widely studied models of experience-dependent plasticity. We have previously defined the time course over which presynaptic development occurs in these two cortical areas, enabling us to make the first direct comparison of the role of sensory experience during synaptic development. We found that maturation of STP in visual cortex was unaffected by dark rearing from before eye opening. In marked contrast, total whisker deprivation completely blocked the developmental decrease in presynaptic release probability (Pr), and the concomitant increase in paired pulse ratio (PPR), which occur in barrel cortex during the third and fourth postnatal weeks. However, the developmental increase in the steady state response to a train of stimuli was unaffected by whisker deprivation. This supports a mechanistic link between Pr and the PPR, but dissociates Pr from the steady state amplitude during repetitive stimulation. Our findings indicate that sensory experience plays a greater role in presynaptic development at L4 to L2/3 excitatory synapses in the barrel cortex than in the visual cortex.